PENGARUH STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN Pada PT Mustika Ratu Tbk (Periode 2014 – 2023) - Larasati, Cipta Ayu; Safii, Mohamad (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This study aims to examine the partial and simultaneous effects of Capital Structure and Financial Performance on Firm Value at PT Mustika Ratu Tbk during the period from 2014 to 2023. The type of research used is quantitative with a descriptive appROAch. Data collection was conducted through documentation studies based on the company’s financial reports. The population in this study consists of all financial reports of PT Mustika Ratu Tbk, while the sample comprises the annual financial statements of PT Mustika Ratu Tbk over the ten-year period. The Capital Structure variable is measured using the Debt to Equity Ratio (DER), Financial Performance is measured using Return on Assets (ROA), and Firm Value is measured using the Price to Book Value (PBV). The analysis results show that, partially, Capital Structure does not have a significant effect on Firm Value, with a t-statistic of 1.290511 < t-table value of 2.30600 and a significance level of 0.2379 > 0.05. However, Financial Performance has a significant effect on Firm Value, with a t-statistic of 4.597290 > t-table value of 2.30600 and a significance level of 0.0025 < 0.05. Simultaneously, Capital Structure and Financial Performance have a significant effect on Firm Value, as indicated by an F-statistic of 15.47391 > F-table value of 4.74 and a significance level of 0.002696 < 0.05. This study emphasizes that Financial Performance plays a more dominant role in influencing investor perception and firm value compared to Capital Structure. Therefore, companies should focus on improving efficiency and profitability to enhance their value in the eyes of the market.